Rapid, simple method for treating clinical specimens containing Mycobacterium tuberculosis to remove DNA for polymerase chain reaction. - Buck, G E (1992)
Several simplified methods for treating mycobacteria to release DNA for amplification by the polymerase chain reaction (PCR) were investigated. The most effective of the methods was sonication. Samples were placed in screw-capped microcentrifuge tubes that were then placed in a plastic rack. The rack was floated in a dish of water next to the ultrasonic probe so that the ultrasonic energy was transmitted through the walls of the tubes. This allowed multiple samples to be processed safely and effectively. Forty-three clinical samples were processed by this procedure, and the crude preparations were analyzed for Mycobacterium tuberculosis by PCR. Twenty-six of these specimens contained M. tuberculosis, and 17 either had no growth or contained other species of mycobacteria. Twenty-four of the 26 (92%) positive specimens were correctly identified, and all of the negative specimens were correctly identified. This sonication procedure appears promising as a rapid, simple means of treating clinical specimens containing mycobacteria for PCR analysis.